2012
DOI: 10.1016/j.juro.2012.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Semen Quality in Men Who Sustained a Spinal Cord Injury During the Prepubertal Period

Abstract: Spinal cord injury before the age of 9 years appears to interfere with spermatogenesis. In subjects injured near the age of 12 years semen quality in adulthood appears to be similar to that of subjects injured as adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
2
3
Order By: Relevance
“…6,10,29 We found no correlation between the age at SCI and semen impairment. In particular, the semen parameters were not different between the patients injured prior to puberty (n = 4; mean age = 3 ± 1.3 years) and after puberty (n = 23; mean age = 23.9 ± 4.9 years, Table S2), which is contrary to the study by Celigoj et al 30 However, considering the very low number of patients included in both studies, definitive conclusions cannot be drawn and a study enrolling more patients injured prior to puberty needs to be conducted. Unlike the studies by Iremashvili et al 10 and Vargas Baquero et al, 31 we did not find that there was an association between the sperm parameters and the completeness of the lesion although the low number of patients studied could explain this difference.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…6,10,29 We found no correlation between the age at SCI and semen impairment. In particular, the semen parameters were not different between the patients injured prior to puberty (n = 4; mean age = 3 ± 1.3 years) and after puberty (n = 23; mean age = 23.9 ± 4.9 years, Table S2), which is contrary to the study by Celigoj et al 30 However, considering the very low number of patients included in both studies, definitive conclusions cannot be drawn and a study enrolling more patients injured prior to puberty needs to be conducted. Unlike the studies by Iremashvili et al 10 and Vargas Baquero et al, 31 we did not find that there was an association between the sperm parameters and the completeness of the lesion although the low number of patients studied could explain this difference.…”
Section: Discussioncontrasting
confidence: 96%
“…We found no correlation between the age at SCI and semen impairment. In particular, the semen parameters were not different between the patients injured prior to puberty ( n = 4; mean age = 3 ± 1.3 years) and after puberty ( n = 23; mean age = 23.9 ± 4.9 years, Table S2), which is contrary to the study by Celigoj et al 30 . However, considering the very low number of patients included in both studies, definitive conclusions cannot be drawn and a study enrolling more patients injured prior to puberty needs to be conducted.…”
Section: Discussioncontrasting
confidence: 96%
“…Furthermore, the pre‐injury fertility of each patient was unknown to us, and we cannot exclude the possibility that some of our patients could have had azoospermia before their injury. In fact, although our data suggested progressive deterioration of spermatogenesis after injury, previous studies have shown no post‐injury decline in semen quality in SCI patients …”
Section: Discussioncontrasting
confidence: 88%
“…Celigoj et al . reported that SCIs that occur before the age of 9 years appear to interfere with spermatogenesis, whereas the semen quality of those injured near the age of 12 years is not impaired . In the present study, only one participant was aged <18 years at the time of injury, thus we could not evaluate the effects of SCI before puberty.…”
Section: Discussionmentioning
confidence: 61%
“…These boys may have impaired spermatogenesis as adults. 75 Many studies have shown hormonal changes after SCI; however, these hormonal changes have not shown clear associations with abnormal semen analysis parameters in men with SCI. 10 …”
Section: Semen Abnormalities In Men With Scimentioning
confidence: 99%